A IMPLEMENTAÇÃO DE PROCEDIMENTOS DE CONTROLE COMO ESTRATÉGIA DE DISSEMINAÇÃO DO CONHECIMENTO E INSTRUMENTO PARA ATINGIR EFICIÊNCIA NA FISCALIZAÇÃO DE CONTRATOS DE SERVIÇOS TERCEIRIZADOS EM UMA UNIVERSIDADE PÚBLICA - Marinho, Rita de Cassia Pinto (2012)
By ordinance, outsourcing services in the public sphere is conducted through administrative contract. To avoid loss to the public Treasury and ensure a more efficient management, it is necessary the truly monitoring and inspecting of the agreed adjustments, increasing the importance of the role of inspectors contracts. This study aims to analyze and discuss the process of supervision of contracts for outsourced services, analysing the inspectors context, who performed their attributions at public university, in the field of knowledge management and innovation. The work is focused on a theoretical framework, based on concepts related to knowledge management, organizational learning and outsourcing as well as its major aspects and challenges in implementing it on public contracts, which have specific laws. The investigation method adopted is the study case; however the scope of this work is being limited to the this institution, the results may serve as a paradigm for similar organizations. The research structure is applied and qualitative approach, in favor of analytical understanding, supported by desk, participatory and field research as well as by literature, direct observation and iterative triangulation between two case studies developed in public institutions. The results pointed out the necessity of actions aimed at professionals involved in the inspection activity, mainly to enhance their competence, in order to repair the identified weaknesses and improve the performance of their routines. In conclusion, by applying control instruments, the monitoring system of contracts have to be improved, in order to increase its efficiency, disseminate knowledge within the institution, and therefore develop a more systematic assessment of contractors service quality under public universities.